Design of Pendhapa Village Room Tour Advertising for PT Nauman Property Group's Tiktok Platform - Amaliah, Fiki; Hendrawan, Aris; Zulfikar, Ali; Farida, Kania (ENCRYPTION: Journal of Information And Technology, 2023)
In the increasingly advanced digital era, TikTok has become a platform that is considered by many groups to promote a product or service, including property providers. However, the design of advertising content on TikTok must still be relevant and attractive according to the style and preferences of its users, who are known to be dynamic and creative. In this study, the author aims to design an advertising video that will be broadcast on PT Nauman Property Group's Tiktok account. The research method used by the author is the research and development (R & D) method. The end result of this research is to provide practical suggestions, such as better use of devices, attention to the characteristics of TikTok, creativity in video concepts, choosing the right music, and analysis of video performance which are expected to help PT Nauman Property Group in optimizing the potential of TikTok.